Inter- and Intramolecular [4+2]-Cycloaddition Reactions with 4,4-Disubstituted N-Silyl-1,4-dihydropyridines as Precursors for N-Protonated 2-Azabutadiene Intermediates - Schmaunz, Cornelia E.; Mayer, Peter; Wanner, Klaus T. (Synthesis, 2014)
An efficient and straightforward method for the synthesis of polycyclic ring systems with a central 2-azabicyclo[2.2.2]octane unit is developed. The process is based on [4+2]-cycloaddition reactions that are performed with N-protonated 2-azabutadiene intermediates as heterodienes, generated from 4,4-disubstituted N-silyl 1,4-dihydropyridines. As dienophiles, cyclopentadiene for the intermolecular cycloaddition and an allyl moiety already attached to the 4,4-disubstituted 1,4-dihydropyridines for the intramolecular variant, are used.
Keywords: hetero-Diels–Alder reaction; 1,4-dihydropyridines; heterocycles; polycycles; imines